RUANG BAIRE DAN FUNGSI â FUNGSI YANG BERKAITAN DENGAN RUANG BAIRE - , NICKY KURNIA TUMALUN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In this thesis, we study some properties related to semi-open, semi-closed, pseudo cover and topological sum on Baireness of topological space. Moreover, we also study some necessary and sufficient conditions of functions that preserve Baire space, induce its domain or codomain to be a Baire space, ô-disconnected set, or second category set.